You can factor a parabola by finding its roots: if
[tex] p(x)=x^2+bx+c [/tex]
has roots [tex] x_1,\ x_2 [/tex], then you have the following factorization:
[tex] p(x) = (x-x_1)(x-x_2) [/tex]
In order to find the roots, you can use the usual formula
[tex] x_{1,2} = \dfrac{-b\pm\sqrt{b^2-4ac}}{2a} [/tex]
In the first example, this formula leads to
[tex] x_{1,2} = \dfrac{-2\pm\sqrt{4+4}}{2} = \dfrac{-2\pm\sqrt{8}}{2} = \dfrac{-2\pm2\sqrt{2}}{2} = 1 \pm \sqrt{2} [/tex]
So, you can factor
[tex] x^2-2x-1 = (x-1-\sqrt{2})(x-1+\sqrt{2}) [/tex]
The same goes for the second parabola.
As for the third exercise, simply plug the values asking
[tex] f(1.5)=-5.25 [/tex]
you get
[tex] f(-1.5) = 1.5c-3 = -5.25 [/tex]
Add 3 to both sides:
[tex] 1.5c = -2.25 [/tex]
Divide both sides by 1.5:
[tex] c = 1.5 [/tex]